2022
DOI: 10.31234/osf.io/dqfyw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The hearing hippocampus

Abstract: The hippocampus has a well-established role in spatial and episodic memory but a broader function has been proposed including aspects of perception and relational processing. Neural bases of sound analysis have been described in the pathway to auditory cortex, but wider networks supporting auditory cognition are still being established. We review what is known about the role of the hippocampus in processing auditory information, and how the hippocampus itself is shaped by sound. In examining imaging, recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 676 publications
0
2
0
Order By: Relevance
“…The hippocampus plays a multifaceted role in information processing and memory, with the right hippocampus generally implicated in spatial navigation and visual memory, while the left hippocampus predominantly engages in perception, learning and recall of speech (Ezzati et al, 2016;Billig et al, 2022). Our results specifically implicate the left hippocampus, consistent with its known lateralization.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The hippocampus plays a multifaceted role in information processing and memory, with the right hippocampus generally implicated in spatial navigation and visual memory, while the left hippocampus predominantly engages in perception, learning and recall of speech (Ezzati et al, 2016;Billig et al, 2022). Our results specifically implicate the left hippocampus, consistent with its known lateralization.…”
Section: Discussionsupporting
confidence: 76%
“…Our results specifically implicate the left hippocampus, consistent with its known lateralization. The hippocampus certainly receives and operates on auditory information (for a review, see Billig et al, 2022), and its pyramidal place cells (O' Keefe and Dostrovsky, 1971) can map out dimensions of sound as they do for space, at least in rodents (Aronov et al, 2017). The hippocampus is also active during auditory working memory (Bishop and Miller, 2009;Davis et al, 2011;Kumar et al, 2016;Lad et al, 2020;Kumar et al, 2021) and may provide predictive information to superior temporal sites during continuous speech listening (Michelmann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible mechanisms for the relationship between hearing impairment and cognitive impairment: common pathology, impoverished input, occupation of cognitive resources and functionpathology interaction (Griffiths et al, 2020). A recent review highlighted the interaction of auditory processing with the hippocampus and the possible outcome on cognition (Billig et al, 2022). Moderate noise exposure in rats specifically impaired neuroplasticity in the hippocampus and cerebral cortex which led to deleterious cognitive outcomes, and a study in gorillas found that a deficit of auditory processes was associated with damage in the integrity of white matter in hippocampus-related structures, leading to extensive cognitive compromise (Gray et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature that the medial temporal lobe including the hippocampus, key brain structures implicated in AD, is involved in auditory processing ( Billig and others 2022 ). Human functional imaging studies demonstrate the involvement of these structures in real-world listening under adverse conditions, such as speech-in-noise perception ( Griffiths and others 2020 ).…”
Section: Does Sensory Loss Cause Dementia?mentioning
confidence: 99%
“…Human functional imaging studies demonstrate the involvement of these structures in real-world listening under adverse conditions, such as speech-in-noise perception ( Griffiths and others 2020 ). Auditory cognition relevant to real-world listening, including working memory for sounds, has been shown to depend on hippocampal mechanisms ( Billig and others 2022 ). Rodent work supports specific roles for medial temporal lobe structures in auditory cognition: Aronov and others (2017) demonstrated that single units in the hippocampus were tuned to specific frequencies during a working memory task, consistent with the use of hippocampal computational mechanisms for auditory analysis.…”
Section: Does Sensory Loss Cause Dementia?mentioning
confidence: 99%